2020
DOI: 10.1099/ijsem.0.003935
|View full text |Cite
|
Sign up to set email alerts
|

Division of the genus Chryseobacterium: Observation of discontinuities in amino acid identity values, a possible consequence of major extinction events, guides transfer of nine species to the genus Epilithonimonas, eleven species to the genus Kaistella, and three species to the genus Halpernia gen. nov., with description of Kaistella daneshvariae sp. nov. and Epilithonimonas vandammei sp. nov. derived from clinical specimens

Abstract: The genus Chryseobacterium in the family Weeksellaceae is known to be polyphyletic. Amino acid identity (AAI) values were calculated from whole-genome sequences of species of the genus Chryseobacterium, and their distribution was found to be multi-modal. These naturally-occurring non-continuities were leveraged to standardise genus assignment of these species. We speculate that this multi-modal distribution is a consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(119 citation statements)
references
References 104 publications
(146 reference statements)
6
110
1
Order By: Relevance
“…The calculated AAI, ANI and dDDH values between the genome sequences of strain GH1-50 T and all the type strains compared in were <70.0, <84.1 and <20.5 %, respectively. Although there is no generalized boundary in prokaryotic genus delineation, a threshold (76 %) for the AAI value was suggested for delineation of bacteria genera [27, 28]. The indices for overall genomic similarity calculated in this study indicated that strain GH1-50 T could be a member of a new genus in the family Rhodobacteraceae .…”
Section: Whole Genome Phylogenymentioning
confidence: 93%
“…The calculated AAI, ANI and dDDH values between the genome sequences of strain GH1-50 T and all the type strains compared in were <70.0, <84.1 and <20.5 %, respectively. Although there is no generalized boundary in prokaryotic genus delineation, a threshold (76 %) for the AAI value was suggested for delineation of bacteria genera [27, 28]. The indices for overall genomic similarity calculated in this study indicated that strain GH1-50 T could be a member of a new genus in the family Rhodobacteraceae .…”
Section: Whole Genome Phylogenymentioning
confidence: 93%
“…These values were below the threshold values of recommended species delineation of ANI at 95–96% [19] and AAI at 95 % [20], indicating that strain S2-4-21 T and MT2-5-19 could be considered to be a novel species. AAI values were also below the cutoff (74–76%) for a novel genus delineation, which were recommended in analysis of Chryseobacterium and its close relatives within the family Weeksellaceae [21]. The genomic relatedness of strains S2-4-21 T and MT2-5-19 in comparison with close relatives together with phylogenetic reconstruction supported that they were distinctly separated from Euzebyella and Pseudozobellia , indicating that strain S2-4-21 T could be considered as a novel species of a novel genus ().…”
Section: Genome Characteristicsmentioning
confidence: 99%
“…On the other hand, the ANI and dDDH values between strain YC2-7 T and members of the family Nocardiaceae were <73.2 and <19.2 %, respectively. These values obtained for the overall genome similarities revealed that the isolates could be assigned to a member of a new genus in the family Nocardiaceae [28, 29].…”
Section: Whole Genome Sequencing and Analysismentioning
confidence: 99%